Reactive pericytes in early phase are involved in glial activation and late-onset hypersusceptibility to pilocarpine-induced seizures in traumatic brain injury model mice - Kenta Sakai; Fuyuko Takata; Gaku Yamanaka; Miho Yasunaga; Kana Hashiguchi; Kazuki Tominaga; Kouichi Itoh; Yasufumi Kataoka; Atsushi Yamauchi; Shinya Dohgu (Elsevier, 2021)
In this study, among neurovascular unit (NVU) cells, we focused on pericyte reactivity in mice subjected to controlled cortical impact (CCI) to understand how traumatic brain injury (TBI) causes uncoordinated crosstalk in the NVU and alters neuronal activity. Histological analyses of brain pericytes, microglia and astrocytes were performed for up to 28 days after CCI in the injured ipsilateral hippocampus. To evaluate altered neuronal activity caused by CCI, we measured seizure susceptibility to a sub-threshold dose of pilocarpine on postoperative day 7, 14, 21 and 28. Platelet-derived growth factor receptor (PDGFR) β immunoreactivity in pericytes significantly increased from 1 h to 4 days after CCI. The expression of Iba1 and GFAP, as markers of microglia and astrocytes, respectively, increased from 4 to 28 days after CCI. The severity of seizure induced by pilocarpine gradually increased, becoming significant at 28 days after CCI. Then, we treated CCI mice with an inhibitor of PDGFR signaling, imatinib, during the postoperative day 0-4 period. Imatinib lowered seizure susceptibility to pilocarpine and suppressed microglial activation in the injured hippocampus at postoperative day 28. These findings indicate that brain pericytes with rapidly increased PDGFRβ expression may drive TBI-induced dysregulation of NVU function and brain hyperexcitability.